Generation of shear Alfvén waves by repetitive electron heating. Issue 1 (11th January 2016) - Wang, Y.; Gekelman, W.; Pribyl, P.; Van Compernolle, B.; Papadopoulos, K.
Abstract: ELF/ULF waves are powerful tools for submarine communication, geophysical mapping, and radiation belt remediation. However, due to their large wavelength (on the order of 10 2 –10 4 km or 0.1–10 RE ) it is difficult to launch them using ground‐based antennas. Alternatively, these waves can be generated by modulating the temperature of the ionosphere using ground‐based HF transmitters. The paper reports a detailed laboratory study on the generation of shear Alfvén waves by repetitive electron heating. The experiments were conducted on the large plasma device at University of California, Los Angeles. In the experiment, 10 pulses of high‐power microwaves (250 kW, 1 µs each) near the plasma frequency modulated at a variable fraction between 0.1 and 1.0 of f ci are launched transverse to the background field. In addition to bulk electron heating the interaction generates a population of fast electrons in the tail of the distribution function. The field‐aligned current carried by the fast electrons acts as an antenna that radiates shear Alfvén waves. It is demonstrated that a shear Alfvén wave at a controllable, arbitrary frequency ( f < f ci ) can be coherently driven by the repetitive microwave pulses. The radiation pattern and power dependence of the virtual antenna are also presented. The experiments provide a novel virtual antenna concept relevant to the equatorial region where the Earth's magnetic field is horizontal and the field‐aligned plasma density gradient is small. The results are important to design of new mobile ionospheric heaters for equatorial and middle latitude locations. Key Points: Equatorial ionospheric HF heating experiment is simulated in a large laboratory plasma A field‐aligned current system is established by heating pulses and advanced by shear Alfven waves Shear Alfven waves at controllable frequencies can be coherently driven by modulated heating pulses